Franco : "caudillo de España - Preston, Paul, 1946-; Camprodón, Teresa (Barcelona : Grijalbo, 1994)
Spaanstalige Franco-biografie.
Keywords: Franco y Bahamonde Salgado, Francisco Paulino Hermenegildo Teódulo, -- 1892-1975.